LABOUR MARKET EFFECTS OF SOCIAL SECURITY CONTRIBUTION REFORM IN SERBIA - Žarković-Rakić, Jelena; Ranđelović, Saša; Vladisavljević, Marko (Economic Annals, 2016)
In Serbia the inactivity rate of the working-age population is close to 40%, among the highest in Europe. The country also faces a high informal employment rate of 24%. Previous research has argued that high levels of informality and inactivity are mostly due to a high effective tax wedge at low wage levels caused by a minimum base for calculation of social security contributions (SSC), sudden withdrawal of means-tested benefits once formal income is earned, and low progressivity of income tax. This paper evaluates the impact of the minimum SSC base reform scenarios on labour supply and employment formalization using tax and benefit micro-simulation models together with the structural discrete choice labour supply model based on the Survey on Income and Living Conditions Data. Although we do not find positive employment effects of the reform, it would be premature to deduce that abolishment of the minimum SSC base is not needed. At this stage in our research, until alternative labour-supply modelling is applied, with both sector and hours of work choice alternatives, it is only safe to conclude that the proposed reform will not significantly contribute to the transformation of informal full-time to formal full-time jobs.